Alcoholic liver disease- Hepatocellular carcinoma transformation - French, Samuel W; Lee, James; Zhong, Jim; Morgan, Timothy R; Buslon, Virgil; Lungo, William; French, Barbara A (Journal of Gastrointestinal Oncology; Vol 3, No 3 (September 01, 2012): Journal of Gastrointestinal Oncology (Current Topics in Gastrointestinal and Liver Pathology), 2012)
No Abstract.